Unveiling a New Antimicrobial Peptide with Efficacy against P. aeruginosa and K. pneumoniae from Mangrove-Derived Paenibacillus thiaminolyticus NNS5-6 and Genomic Analysis - Namfa Sermkaew; Apichart Atipairin; Sucheewin Krobthong; Chanat Aonbangkhen; Yodying Yingchutrakul; Jumpei Uchiyama; Nuttapon Songnaka (MDPI AG, 2024)
This study focused on the discovery of the antimicrobial peptide (AMP) derived from mangrove bacteria. The most promising isolate, NNS5-6, showed the closest taxonomic relation to Paenibacillus thiaminolyticus, with the highest similarity of 74.9%. The AMP produced by Paenibacillus thiaminolyticus NNS5-6 exhibited antibacterial activity against various Gram-negative pathogens, especially Pseudomonas aeruginosa and Klebsiella pneumoniae. The peptide sequence consisted of 13 amino acids and was elucidated as Val-Lys-Gly-Asp-Gly-Gly-Pro-Gly-Thr-Val-Tyr-Thr-Met. The AMP mainly exhibited random coil and antiparallel beta-sheet structures. The stability study indicated that this AMP was tolerant of various conditions, including proteolytic enzymes, pH (1.2-14), surfactants, and temperatures up to 40 °C for 12 h. The AMP demonstrated 4 µg/mL of MIC and 4-8 µg/mL of MBC against both pathogens. Time-kill kinetics showed that the AMP acted in a time- and concentration-dependent manner. A cell permeability assay and scanning electron microscopy revealed that the AMP exerted the mode of action by disrupting bacterial membranes. Additionally, nineteen biosynthetic gene clusters of secondary metabolites were identified in the genome. NNS5-6 was susceptible to various commonly used antibiotics supporting the primary safety requirement. The findings of this research could pave the way for new therapeutic approaches in combating antibiotic-resistant pathogens.